Beyond Essentialism: Women’s Ecological Agency and Traditional Ecological Knowledge in Kampung Adat Dukuh, Garut, West Java, Indonesia - Gina Giftia Azmiana Delilah; Neng Hannah; Amadea Selma Agnia Elfath; Nur Syakiran Akmal Ismail (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2025)
The global environmental crisis needs a critical reevaluation of traditional knowledge systems and gender dimensions in ecological management. This study examines the ecological role of women in Kampung Adat Dukuh, Garut, West Java, Indonesia, from a materialist ecofeminist perspective to deconstruct essentialist assumptions regarding women's “natural” closeness to nature. Utilizing qualitative ethnographic methods, this study highlights how women, often marginalized in Traditional Ecological Knowledge (TEK), act as vital ecological mediators. Their practices, including ritual leadership and subsistence work, demonstrate that ecological agency is socially constructed rather than biologically inherent. This research positions indigenous women as active contributors, enhancing ecofeminist theory and informing gender-sensitive conservation strategies that recognize the socio-political aspects of women's labor.